2011
DOI: 10.1073/pnas.1009878108
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the missing baryons in clusters

Abstract: Observations of clusters of galaxies suggest that they contain fewer baryons (gas plus stars) than the cosmic baryon fraction. This "missing baryon" puzzle is especially surprising for the most massive clusters, which are expected to be representative of the cosmic matter content of the universe (baryons and dark matter). Here we show that the baryons may not actually be missing from clusters, but rather are extended to larger radii than typically observed. The baryon deficiency is typically observed in the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
4
8
0
Order By: Relevance
“…Using the SDSS photometric data for A1835 and A1689, the authors found that the hot regions are associated with a filamentary structure, while the cold regions contact low-density regions outside the clusters. Finally, the increasing f gas profile at r 0.3R reported in Figure 3 confirms the conclusion of Rasheed et al (2010) that the baryons are not missing. They are simply located in the most peripheral regions of the clusters likely for the heating processes (such as shock heating of the gas, supernovae, and AGN feedback) that cause the ICP to expand or hinder its inflow.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Using the SDSS photometric data for A1835 and A1689, the authors found that the hot regions are associated with a filamentary structure, while the cold regions contact low-density regions outside the clusters. Finally, the increasing f gas profile at r 0.3R reported in Figure 3 confirms the conclusion of Rasheed et al (2010) that the baryons are not missing. They are simply located in the most peripheral regions of the clusters likely for the heating processes (such as shock heating of the gas, supernovae, and AGN feedback) that cause the ICP to expand or hinder its inflow.…”
Section: Discussionsupporting
confidence: 72%
“…The total baryon fraction (f b = f gas + f stars ) and its evolution with the redshift are used to constrain cosmological parameters since it is believed to be representative of the universe (e.g., White et al 1993;Metzler & Evrard 1994;Ettori et al 2009). Current studies have shown that the cluster baryon fraction f b derived at r 500 is lower than the ratio Ω b /Ω M measured from the cosmic microwave background (CMB) by several experiments (Afshordi et al 2007;Umetsu et al 2009;Vikhlinin et al 2006;Arnaud et al 2007;Sun et al 2009;Komatsu et al 2011) raising the question of where the missing baryons are allocated (Rasheed et al 2010). To address this issue, Landry et al (2012) recently used Chandra X-ray observations to measure the gas mass fraction for a complete sample of massive clusters in the redshift range 0.15-0.30 from the brightest cluster sample (Ebeling et al 1998;Dahle 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been solved. For a relatively large sample of groups and clusters of galaxies the gas fraction has been measured within r500 and it is concluded that the "missing" baryons are present as X-ray gas located in the outskirts of the clusters (Rasheed et al 2011). Our gas data have allowed an extrapolation which confirms this picture.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, in our model, we made a rather ad hoc assumption that the gas that is removed from the central regions is on the outskirts of the haloes. Although this seems plausible (see, for example Rasheed, Bahcall & Bode 2010) it is not clear how accurately one can observe the distribution of the gas on the outskirts of the haloes. Because of those observational limitations, we expect that an accurate description of the baryonic feedback will have to rely in part on simulations.…”
Section: Reducing the Bias Using A Simple Modelmentioning
confidence: 99%